Arbuscular Mycorrhizal Fungus Rhizophagus irregularis Influences Artemisia annua Plant Parameters and Artemisinin Content under Different Soil Types and Cultivation Methods - Domokos, Erzsébet (Microorganisms, 2020)
Artemisinin extracted from Artemisia annua has been used efficiently in malaria treatment since 2005. In this study, the variations in plant parameters (plant biomass, glandular trichome density, essential oil total chemical content, artemisinin production, and polyphenol oxidase (PPO) activity) were tested under different soil types (Luvisol, Gleysol, Anthrosol and sterile peat) and cultivation conditions (potted plants in semi-open field, and open field experiments) for plants inoculated with arbuscular mycorrhizal fungus (AMF) Rizophagus irregularis. Under semi-open field conditions, the AMF colonization of A. annua plant roots varied, and presented the highest percentage in Luvisol and sterile peat. The increase in the root colonization rate positively influenced some plant parameters (biomass, glandular trichome density, artemisinin concentration, essential oil quantity and composition), but no effects on PPO enzyme activity were detected. AMF fungus R. irregularis significantly increased the artemisinin content and essential oil yield of plants cultivated in Luvisol, Gleysol, Anthrosol and in peat. These soil types can offer appropriate conditions for A. annua cultivation and artemisinin production even on a smaller scale. Under open field conditions, low (about 5%) AMF colonization was observed. No differences in artemisin contents were detected, but essential oil yield significantly increased compared to control plants. AMF treatment increased beta-farnesene and germacrene D concentrations in Artemisia plants in the open field experiment.